THE EFFICACY OF BIFOCAL RIGHT VENTRICULAR PACING IN CARDIAC RESYNCHRONIZATION THERAPY FOR THE TREATMENT OF HEART FAILURE - Darya Saeed; Nasreen Wafi; Jawad Hawas; Amar Al-Hamdi; Dana Marif (European Scientific Journal, ESJ, 2013)
Background: It has been reported that bifocal pacing (BiFP) in the right ventricle (RV) may be an alternative to unsuccessful left ventricular (LV) lead implantation.Aim: This study seeks to assess the improvement in the clinical and hemodynamic parameters after long term BiFP in patients eligible for cardiac resynchronization therapy (CRT), in whom conventional biventricular (BiV) implantation was not feasible or failed.Methods: The three leads (right atrial appendage, RV apex and RV outflow tract) of a BiFP were implanted in 46 patients, among whom16 lost follow up within one month of BiFP implantation, so 30 patients (19 male/11 female) were enrolled in the study with the mean follow up period of 8.7 (± 6.7) months. All patients had heart failure refractory to medical therapy, New York Heart Association (NYHA) functional class of II, III and IV, ejection fraction (EF) ≤ 35 %, left bundle branch block (LBBB) with QRS duration ≥ 130 milliseconds and functional mitral regurgitation. The parameters (QRS duration, NYHA class, EF, and cardiomegaly) were evaluated before and 1, 3, 6, 12 and 24 months after BiFP implantation. A six minute walk test (6MWT) was performed on 7 patients, before and after implantation.Results: The results showed significant improvement in whole parameters, after both acute and long term BiFP. The improvement increased during subsequent follow up.Conclusions: The study concluded that BiFP is a feasible type of CRT in patients with refractory HF and can be used as an alternative to biventricular pacing when LV lead implantation is infeasible.